Manajemen Risiko Berdasarkan ISO 45001:2018 - Luqmantoro, Luqmantoro; Yuliana, Lina; Zainul, L.M.; Saputera, Dharma; Zainal , M.Isradi (Program Studi D4 K3 Universitas Balikpapan, 2022)
Management System is a framework of processes and procedures used to ensure whether a company or organization can meet standards and carry out their duties to achieve organizational goals. Based on Government Regulation of the Republic of Indonesia Number 50 of 2012 concerning Application of Occupational Health and Safety Management System Article 5 paragraphs 1 – 4, companies are required to implement SMK3 if the company has workers/laborers of at least 100 (one hundred) people, or has a high level of potential danger. Companies in implementing SMK3 must be guided by this Government Regulation and the provisions of laws and regulations and can pay attention to international conventions or standards. With the implementation of ISO 45001:2018 it is considered necessary and relevant to be applied in every company as an effort to prevent work accidents and occupational diseases. The method of community service is carried out online through the Zoom meeting application. Participants in the implementation are company employees and the general public. The target in this activity is to increase knowledge for the company in order to improve the safety management system.